Tindak Tutur Ilokusi dalam Serial Kartun “Urwah Ibnu Zubair” Kajian Pragmatik - Elia Nurul Hidayati; Khansa Haura Ramadhani; Fahmy Lukman (Ukazh : Journal of Arabic Studies, 2026)
Animated films are literary works that convey a narrative message through visual and audio elements, and have spread worldwide via the YouTube platform. This study aims to describe the narrative structure and the functions of illocutionary speech acts found in the animated series “Urwah Ibnu Zubair” on the YouTube channel Sukardi Hasanudin. The study employs a pragmatic approach using Searle’s (1979) theory of speech acts. Searle (1979) divides illocutionary speech acts into five types, namely (1) assertive, (2) directive, (3) expressive, (4) commissive, and (5) declarative. This study is a qualitative descriptive study involving a series of written words at the analysis stage and the presentation of the analysis results. The data were obtained by analysing the dialogue between characters using the ‘listen and note’ technique. Based on the results of data collection and classification, 86 illocutionary acts were identified, comprising 25 assertive illocutionary acts, 30 directive acts, 26 expressive acts and 4 commissive acts; no declarative acts were found. The analysis and results show that the dominant speech acts were directive (30), which served to propose, advise, ask questions, and instruct. Additionally, there were equal numbers of assertive and expressive speech acts (26 instances each), which served to state, explain, and report, as well as utterances related to the psychological state of the addressee. Based on this, the language in this animated film functions as a means of conveying information. The language and speech acts in this cartoon also depict the characters, emotions, and moral values of the characters. Thus, the animated film Urwah Ibnu Zubair is not only a medium of entertainment but also an educational tool that reflects Islamic values through the use of communicative and meaningful language.